2022
DOI: 10.1371/journal.pone.0272959
|View full text |Cite
|
Sign up to set email alerts
|

Towards universal health coverage: The level and determinants of enrollment in the Community-Based Health Insurance (CBHI) scheme in Ethiopia: A systematic review and meta-analysis

Abstract: Background Community-based health insurance (CBHI) is a risk-pooling approach that tries to disperse health expenditures across families with varying health profiles to provide greater access to healthcare services by allowing cross-subsidies from wealthy to poor populations. It is crucial to assess the level of CBHI enrolment and its determinants in Ethiopia, where government health spending is limited to less than 5% of GDP, far below the Alma Ata Declaration’s benchmark of 15%. Although various epidemiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…Thus, enrolling in health insurance schemes allows them to become more familiar with existing service delivery points. The finding lends support to the notion that removing direct financial barriers through health insurance schemes may increase maternal healthcare utilization in Ethiopia [ 66 , 68 , 69 ]. In addition to maternal care issues, health insurance may act as a pro-poor equalizing agent in health financing by increasing access to health care [ 69 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, enrolling in health insurance schemes allows them to become more familiar with existing service delivery points. The finding lends support to the notion that removing direct financial barriers through health insurance schemes may increase maternal healthcare utilization in Ethiopia [ 66 , 68 , 69 ]. In addition to maternal care issues, health insurance may act as a pro-poor equalizing agent in health financing by increasing access to health care [ 69 ].…”
Section: Discussionsupporting
confidence: 67%
“…The finding lends support to the notion that removing direct financial barriers through health insurance schemes may increase maternal healthcare utilization in Ethiopia [ 66 , 68 , 69 ]. In addition to maternal care issues, health insurance may act as a pro-poor equalizing agent in health financing by increasing access to health care [ 69 ]. Hence, the local administrative authorities should make efforts to make households enroll in health insurance schemes.…”
Section: Discussionsupporting
confidence: 67%
“…The paralleling of these two programmes, in perspective with other experiences in Rwanda, Ghana, Ethiopia44 45 and soon in Benin, to better integrate mutuality into a broader national health financing mechanism, shows that technical and institutional solutions exist and are proven. In Ghana, the NHIS (National Health Insurance Scheme) programme ‘was the subject of a presidential review in 2017.…”
Section: Discussionmentioning
confidence: 93%
“…Based on the concepts of UHC, the qualitative findings of the included studies were thematized into five categories. PC : The PC of the CBHI has gradually been expanded [ 38 , 41 , 42 ]. HSU : CBHI improved HSU [ 36 , 43–56 ], such as antenatal care (ANC) visits [ 43 ]; child healthcare visits [ 44 , 47 ]; seeking treatment for malaria [ 46 ]; in-patient [ 36 ] and outpatient [ 49 , 50 ] attendances; frequency of visits [ 49 , 53 ]; and family planning [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pooled UHC by CBHI was found to be 45.6%. Regarding PC, according to the three national studies included in this review, 40.10% of the households were found to be covered by the scheme, with the lowest, medium, and highest coverages being 28% [ 38 ], 45% [ 42 ], and 45.5% [ 41 ], respectively. Coming to the impact of CBHI on HSU, the pooled report of the 13 included studies showed that the HSU among CBHI members was 64.5%.…”
Section: Resultsmentioning
confidence: 99%